Планирование новой техники: справочник - Александрова В. П. Валентина Петровна; Гарцман Я. Д. Янина Давидовна; Загорская Т. П. Татьяна Павловна; Калашников Б. В. Борис Владимирович (Киев, Технiка, 1982)
Авт. указаны на 4-й с.